Prevalence and Clinical Assessment of Dry Eyes in Lebanon - Fadel, Demi; Othman, Hiba; El Ballouz, Haytham (International Journal of Innovative Research in Medical Science, 2025)
This cross-sectional prospective cohort study investigates the clinical prevalence of dry eye disease (DED) in Lebanon. It is the first clinical study of its kind in Lebanon. Using the Ocular Surface Disease Index (OSDI) questionnaire, patients initially underwent symptoms evaluation. Following this, participants received comprehensive ocular examinations, including the Tear Film Break-Up Time (TBUT), ocular surface staining, Schirmer’s test, and assessment of Meibomian gland quality and expressibility. Our findings indicate a high prevalence of DED, with 73.9% of participants exhibiting symptoms, stratified into mild (32.4%), moderate (19.7%), and severe (47.9%) cases. The mean OSDI score was 33.31 (SD = 14.77). TBUT measurements averaged 6.5 and 6.85 in the right and left eyes, respectively. Ocular surface staining among DED patients was graded across four levels, with most eyes classified between Grades 1 and 3. Schirmer's test results showed reductions of 20% in the right eye and 31% in the left eye. Analysis of Meibomian gland quality and expressibility revealed that Grade 0 was present in 52.1% of cases, Grade 1 in 36.6%, and Grade 2 in 11.3%. Our study identified smoking, contact lens use, and dyslipidemia as prevalent associated conditions, with a statistically significant association between these factors and DED (p < 0.001). Overall, our results confirm a high prevalence of DED in the Lebanese population, with modifiable risk factors that contribute to disease onset and severity.